The development of confocal arthroscopy as optical histology for rotator cuff tendinopathy - Wu, Ping; Walton, M.; Wang, A.; Anderson, P.; Wang, T.; Kirk, T.; Zheng, M. (Blackwell Publishing Ltd, 2015)
MRI, ultrasound and video arthroscopy are traditional imaging technologies for noninvasive or minimal invasive assessment of the rotator cuff tendon pathology. However, these imaging modalities do not have sufficient resolution to demonstrate the pathology of rotator cuff tendons at a microstructural level. Therefore, they are insensitive to low-level tendon diseases. Although traditional histology can be used to analyze the physiology of rotator cuff tendons, it requires biopsy that traumatizes the rotator cuff, thus, potentially comprising the mechanical properties of tendons. Besides, it cannot offer real-time histological information. Confocal endoscopy offers a way to assess the microstructural disorder in tissues without biopsy. However, the application of this useful technique for detecting low-level tendon diseases has been restricted by using clinical grade fluorescent contrast agent to acquire high-resolution microstructural images of tendons. In this study, using a clinical grade sodium fluorescein contrast agent, we have reported the development of confocal arthroscopy for optical histological assessment without biopsy. The confocal arthroscopic technique was able to demonstrate rotator cuff tendinopathy in human cadavers, which appeared macroscopically normal under video arthroscopic examinations. The tendinopathy status of the rotator cuff tendons was confirmed by corresponding traditional histology. The development of confocal arthroscopy may provide a minimally invasive imaging technique for real-time histology of rotator cuff without the need for tissue biopsy. This technique has the potential for surgeons to gain in real time the histological information of rotator cuff tendons, which may assist planning repair strategies and potentially improve intervention outcomes.